The antiviral drug ribavirin is a selective inhibitor of S-adenosyl-L-homocysteine hydrolase from Trypanosoma cruzi - Cai, Sumin (2007)
Ribavirin (1, 2, 4-triazole-3-carboxamide riboside) is a well-known antiviral drug. Ribavirin has also been reported to inhibit human S-adenosyl-L-homocysteine hydrolase (Hs-SAHH), which catalyzes the conversion of S-adenosyl-L-homocysteine to adenosine and homocysteine. We now report that ribavirin, which is structurally similar to adenosine, produces time-dependent inactivation of Hs-SAHH and Trypanosoma cruzi SAHH (Tc-SAHH). Ribavirin binds to the adenosine-binding site of the two SAHHs and reduces the NAD(+) cofactor to NADH. The reversible binding step of ribavirin to Hs-SAHH and Tc-SAHH has similar K(I) values (266 and 194 μM), but the slow inactivation step is five fold faster with Tc-SAHH. Ribavirin may provide a structural lead for design of more selective inhibitors of Tc-SAHH as potential anti-parasitic drugs.